COMMON PROBLEMS CENTRAL ASIAN STUDENTS FACE IN ACADEMIC ENGLISH WRITING - Fotima Kuldosheva,; Karima Rakhmonberdiyeva, (TADQIQOTLAR, 2026)
Abstract: The main purpose of this article is to highlight significant challenges for many Central Asian countries caused by educational, linguistic and cultural factors. Learners  usually  face  difficulties  adopting  academic  writing  norms  required  by academic institutions. This article will provide the most common writing difficulties encountered  by  Central  Asian  students,  discusses  limited  academic  vocabulary, organizational challenges, citation difficulties, linguistic interference as well as cultural background differences. This paper also involves pedagogical implications to enhance student’s academic writing skill.